Anthropogenically forced change in aquatic ecosystems: Reflections on the use of monitoring, archival and palaeolimnological data to inform conservation. Issue 1 (13th May 2020) - Roberts, Lucy R.; Bishop, Isabel J.; Adams, Jennifer K.
Abstract : The open collection "Aquatic transitions: Tracking the nature and trajectories of anthropogenically forced change in freshwater and coastal ecosystems" stems from a session of the same name at the ASLO (Association for the Sciences of Limnology and Oceanography) Aquatic Sciences Meeting 2017 in Honolulu, Hawai'i. The five papers gathered here reflect the focus of the special session on long‐term ecosystem research and monitoring (LTERM), and collectively make use of monitoring data, palaeolimnology, and historical and documentary records to explore the timing, extent, and causes of human‐related impacts on aquatic ecosystems. Collectively, they demonstrate that because timescales of ecological change often extend beyond contemporary monitoring, LTERM plays a crucial role in supporting evidence‐based conservation. In this introduction, we reflect on the role that LTERM has had in each of the ecosystems studied, and discuss the opportunities for LTERM work to inform future conservation. Abstract : The five papers gathered for the open collection 'Aquatic Transitions: Tracking the nature and trajectories of anthropogenically forced change in freshwater and coastal ecosystems' reflect on long‐term ecosystem research and monitoring (LTERM), and collectively make use of monitoring data, palaeolimnology, and historical and documentary records to explore the timing, extent, and causes of human‐related impacts on aquatic ecosystems. In this introduction, we reflect on the role that LTERM has had in each of the ecosystems studied, and discuss the opportunities for LTERM work to inform future conservation. e00089